(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
Ways to increase the energy efficiency of agricultural equipment in relation to processing and food industries are considered, in particular due to excessive and unjustified consumption of electricity during the separation of grain mixtures. It has been proven that cleaning grain from impurities improves storage conditions, reduces transportation costs, reduces grain contamination by pests, and improves the quality of food raw materials used for production. The problem of separation of grain mixtures on modern grain cleaning machines is analyzed from the point of view of their energy efficiency. The choice of methods with minimum consumption of electrical energy for the process of grain separation is offered, which is guaranteed by the differences in the basic physical and mechanical properties of the grain material. The energy efficiency of the use of grain cleaning machines, which ensure the process of dividing the grain mass into fractions according to the set of physical and mechanical properties relative to one working body, is substantiated. Ways of reducing the energy consumption for the separation of grain mixtures to a minimum are proposed. An algorithm for the separation of grain mixtures, taking into account the minimization of energy consumption on modern grain cleaning machines, and an algorithm for the separation of hard-to-separate grain mixtures, using the equipment developed by the authors, have been developed. It is shown that with the help of gravitational shock separators developed by the authors for separating grain mixtures according to their elastic properties, it is possible to clean the seeds of many agricultural crops from weeds and impurities that are difficult to separate. The results of the separation of millet seeds with 6.2% contamination by mouse and chicken millet seeds, and the results of the separation of pea seeds with 5.9% contamination with its halves are given. It was established that 81.6% of millet seeds and 89.2% of pea seeds of the 1st class can be obtained in one pass of the mixtures without spending energy on the separation process.